Management of Hypotony Maculopathy: Poster Presentation - Case Report - Ophthalmologist - Nanditya, Sri Astri; Ayudianingrum, Asti; Sulastiwaty, Rini (Majalah Oftalmologi Indonesia, 2023)
Introduction : Hypotony is a common complicatons after glaucoma filtering surgery. Hypotony maculopathy is a serious condition that related to the significant decrease in visual acuity. This case report is to show the case of hypotony maculopathy and the risk factors. Case Illustration : A 28 yo female with juvenile glaucoma undergone trabeculectomy on her left eye. One day post surgery show significant inflamation forming fibrin in pupil area. POD 1 IOP decreased to 2 mmHg and remains hypotony after 2 weeks post surgery. Visual acuity decreased significantly even when the anterior chamber inflamation has resolved. Funduscopy showed typical appearance of hypotony maculopathy. Oral steroid of methylprednisolon 1 mg/kg per body weight, and topical prednisolon was administered since POD 1. Visual acuity gained and iop rised to 14 after 3 weeks with theraphy with oral and topical steroid. Discussion : Sudden drop of intraocular pressure may lead to many complications such as hipotony maculopathy. It was a frightening as it may decreased the visual acuity permanently. Young age and severe post operative inflamation are risk factors found in this patient. Conclusion : Hypotony after glaucoma filtering surgery may caused hypotony maculopathy. Young age and high inflamation are risk factors for developing hypotony maculopathy. Risk factors considerations and early treatment of hypotony is essential to prevent the sight threatening complications such as hypotony maculopathy.